The 'filtering effects' of ECtHR case law on religious freedoms: legal recognition and places of worship for religious minorities in Greece. Issue 3 (2nd October 2017) - Markoviti, Margarita
ABSTRACT: Greece has received an exceptional number of convictions in religious freedoms cases by the European Court of Human Rights (ECtHR). Looking beyond the implementation/nonimplementation dimension, this study explores the ways in which ECtHR case law is diffused amongst religious minority groups 'on the ground' over two current debates: the legal status of religious minority groups and their right to found and run places of worship. Drawing on empirical research with a range of actors across the spectrum of religious pluralism, the original findings demonstrate that the actual groups pursuing their rights in Strasbourg, namely Jehovah's Witnesses and the Catholic Church of Canea, enjoy the direct impact of the Court's judgements. By contrast, the impact of such jurisprudence is more limited for other minority religious groups in the country. This contribution introduces the notion of 'filtering effects' of the ECtHR, whose case law influences religious minority communities through Jehovah's Witnesses' litigation, which acts as a source of inspiration and rights-awareness for the pursuit of their religious rights claims and mobilisations.